Exploring wobbling motion in triaxial even-even nuclei - Y.M. Wang; Q.B. Chen (Physics Letters B)
The potential presence of wobbling motions in even-even nuclei 112Ru, 114Pd, 150Nd, and 188Os are explored by the five-dimensional collective Hamiltonian based on the relativistic density functional theory (5DCH-RDFT). The theoretical results successfully reproduce experimental energy spectra and electromagnetic transition probabilities. Analyses of the potential energy surfaces and probability density distributions in the (β,γ) deformation plane as well as the quadrupole asymmetry parameter 〈cos⁡3δ〉 reveal that 150Nd shows near-axial symmetry in contrast to the triaxial deformation in 112Ru, 114Pd, and 188Os. Additionally, spin coherent state (SCS) map is introduced for the first time to the 5DCH framework to visualize the geometry of angular momentum. It is revealed that the wobbling mode, characterized by oscillations of total angular momentum J about the medium axis, is present in 112Ru but absent in 150Nd.